POTENTIAL OF MENIRAN LEAF EXTRACT ON NEWCASTLE DISEASE ANTIBODY TITER IN BROILERS - Widiawati, Citra; Suardana, Ida Bagus Kade; Kencana, Gusti Ayu Yuniati; Setiasih, Ni Luh Eka; Nindhia, Tjokorda Sari; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2024)
Newcastle Disease (ND) is one of the infectious diseases that easily attack broilers. Vaccinations carried out to optimize chicken immunity often get unsatisfactory results, so green meniran (Phyllanthus niruri Linn.) is needed as an immunostimulator. Green meniran leaf extract contains flavonoid compounds as the main component to trigger T cells to help B cells to produce antibodies. This study aims to determine the effect of meniran leaf extract (Phyllanthus niruri Linn.) on booster vaccinated broilers on ND antibody titer. The research design used was a complete randomized design in a nested pattern with a total of 30 broilers divided into three treatment groups, namely 10 broilers not given the ND La Sota booster vaccine and not given meniran leaf extract but given a placebo (K-), 10 broilers given the ND La Sota booster vaccine without meniran leaf extract (K+), and 10 broilers given the ND La Sota booster vaccine and meniran leaf extract in drinking water for seven days before and 14 days after vaccination (P). The samples used were one day before booster vaccination (9-day-old broilers), one week after booster vaccination (17-day-old broilers) and two weeks after booster vaccination (24-day-old broilers). Serum obtained was examined serologically by hemagglutination inhibition (HI) test. The data obtained were analyzed statistically Analysis of Variance (Anova) with a significant level of 5% and regression analysis using SPSS (Statistical Product and Service Solution) software. The results showed that in the administration of meniran leaf extract(Phyllanthus niruri Linn.) and the effect of sampling time after ND booster vaccination had an increase in ND antibody titer which was significantly different (P < 0.05) in treatment P with a mean of 2.8; 4.3; 7.1 and a total mean of 4.7 (titer in HI log 2). Regression analysis showed that the P treatment had the highest increase in the third week after ND booster vaccination compared to the K- and K+ treatments.